Особенности эксплуатации пистолетов со свободной отдачей затвора при использовании боеприпасов послегарантийных сроков хранения - Бирюков, А. И. (НТУ "ХПИ", 2013)
В статті розглядається наукова задача, стосовно особливостей короткоствольної зброї з вільною віддачею затвора при застосуванні боєприпасів післягарантійних термінів зберігання.

In article the scientific task, concerning features of operation of guns with free return of a lock when using ammunition after-guarantee periods of storage is considered.
Features of operation of guns with free return of the lock when using ammunition after-guarantee periods of storage
Keywords: стрелковое оружие; артиллерийские системы; арсенал; системы вооружения; пироксилиновые пороха